1994
DOI: 10.1089/jam.1994.7.217
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antibiotic Aerosol Generation Using Commercial Jet Nebulizers

Abstract: The performance of 14 commercial jet nebulisers has been assessed; Unineb, Suremist (Unimed (UK) Ltd), Micro-Cirrus (Intersurgical Ltd), Pulmo-Neb (DeVilbiss Health Care UK Ltd), Side-Stream (Medic-Aid Ltd), Micro-Neb III (Lifecare Ltd), RespirGard (Marquest Medical Products Inc), Aeromist, Venticaire (S and W Vickers Ltd), Up-Draft II, Ava-Neb, Up-Draft (Hudson Respiratory Care Inc), Bennett/Twin, Raindrop (Puritan-Bennett Corporation). The units were operated with a high flow compressor (Maxi III, Medix Ltd)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…This is not the first study to illustrate the in vitro differences in nebulizer performance, but it is unique in demonstrating the impact of the V D on the efficiency of a device with regards to total nebulized drug output when the effect of evaporative losses are taken into consideration. The RF observed for the four devices is within the range reported in previous studies (14,15,19,29). Hess et al (6) reported V D data, unfortunately nebulizer specific comparisons were not possible because the data in this study were pooled for all nebulizer types for different flow and volume settings.…”
supporting
confidence: 79%
See 4 more Smart Citations
“…This is not the first study to illustrate the in vitro differences in nebulizer performance, but it is unique in demonstrating the impact of the V D on the efficiency of a device with regards to total nebulized drug output when the effect of evaporative losses are taken into consideration. The RF observed for the four devices is within the range reported in previous studies (14,15,19,29). Hess et al (6) reported V D data, unfortunately nebulizer specific comparisons were not possible because the data in this study were pooled for all nebulizer types for different flow and volume settings.…”
supporting
confidence: 79%
“…For the purpose of this investigation, as in keeping with other studies (1,6,18,19), 30 s without aerosol production was identified as end nebulization. In the trials using the Updraft II, the generation of intermittent aerosol was limited, and, thus, it was easy to assess this endpoint.…”
Section: Figure 2) Mean Respirable Fraction Within a 95% CI At Flows mentioning
confidence: 89%
See 3 more Smart Citations